Mitochondrial Metabolism Modulates Differentiation and Teratoma Formation Capacity in Mouse Embryonic Stem Cells - Schieke, Stefan M.; Ma, Mingchao; Cao, Liu; McCoy, J. Philip; Liu, Chengyu; Hensel, Nancy F.; Barrett, A. John; Boehm, Manfred; Finkel, Toren (The Journal of biological chemistry, 2008)
Relatively little is known regarding the role of mitochondrial metabolism in stem cell biology. Here we demonstrate that mouse embryonic stem cells sorted for low and high resting mitochondrial membrane potential (ΔΨmL and ΔΨmH) are indistinguishable morphologically and by the expression of pluripotency markers, whereas markedly differing in metabolic rates. Interestingly, ΔΨmL cells are highly efficient at in vitro mesodermal differentiation yet fail to efficiently form teratomas in vivo, whereas ΔΨmH cells behave in the opposite fashion. We further demonstrate that ΔΨm reflects the degree of overall mammalian target of rapamycin (mTOR) activation and that the mTOR inhibitor rapamycin reduces metabolic rate, augments differentiation, and inhibits tumor formation of the mouse embryonic stem cells with a high metabolic rate. Taken together, our results suggest a coupling between intrinsic metabolic parameters and stem cell fate that might form a basis for novel enrichment strategies and therapeutic options.